Research of Real Time Optimization of Gear for DCT Vehicle Under the Ramp - Ding Hua; Xu Cong (Jixie chuandong)
Aiming at the problem of frequent shift phenomenon of the vehicle running in the uphill condition,and the unexpected upshift phenomenon of the vehicle running in the downhill condition. The value of slope is identified based on the EKF algorithm and the dynamics model of ramp. On the basis of ramp identification model and traditional shift schedule,a real time online optimization of dual clutch transmission（ DCT） gear is presented based on fuzzy control method. A simulation model of vehicle fuzzy shift control is established by using MATLAB/Simulink,and the simulation and comparison analysis of the shift schedule of the vehicle before and after the optimization are carried out. The results indicate that the optimized vehicle shift schedule could effectively avoid the frequent shift and unexpected upshift of vehicle. The riding comfort of driver and the vehicle safety are improved.